The development of a course recommendation system for e-learning students. (1st January 2012) - Nishino, Kazunori; Iribe, Yurie; Mizuno, Shinji; Aoki, Kumiko; Fukumura, Yoshimi
It is expected nowadays to develop an e-learning system which provides the learning environment suitable for each individual learner's learning style. In this study, the authors developed a method to recommend courses that are suitable for a student. A student's course adaptability for a particular course can be estimated based on the result gained from a questionnaire which is conducted prior to the beginning of the course by using the multiple regression models that has been derived from the past students' data. The validity of the developed method was confirmed to some extent by applying the method to assess the student's course adaptability for each course. Furthermore, this paper explains the functions of the e-learning course recommendation system that can be added by using the method.